A NEW SPECIES OF SCHIZOSTACHYUM (POACEAE: BAMBUSOIDEAE) FROM SUMBA ISLAND, INDONESIA - I PUTU GEDE P. DAMAYANTO; ELIZABETH A. WIDJAJA (Reinwardtia, 2016)
DAMAYANTO, I P. G. P. & WIDJAJA, E. A. 2016. A new species o Schizostachyum (Poaceae: Bambusoideae) from Sumba Island, Indonesia. Reinwardtia 15(2): 119 – 122. — Schizostachyum purpureum Damayanto & Widjaja is a new species from Sumba Island. Its description and illustration are presented.